Réponses

2014-10-28T16:02:04+01:00
1) tu remplace le x par sa valeur comme suit
a) x= -1.8
 A= 3*(- 1.8) -5  = -10.4
b) x= 0
A=3*(0) -5 = -5
2) aussi c'est la méme chose remplace le x
a) x=-3
B= 5( -3-4) - 6(-3+2)= -29
b) x=2
B= 5 (2-4) - 6(2+2) = -34

2014-10-28T16:08:04+01:00
Faut juste remplacer x par le nombre

1.a)  si x=-1.8   A=3*(-1.8)-5 = - 5.4 -5 = 0.4 . 
 b) Si x=0 A= 3*0-5 = 0-5 = -5 

2.a)  si x=-3  B=5(-3-4)-6(-3+2) =  5(-7) - 6(-1) = -35 - (-6) = -35+6 = -29.
b) x=2  B=5(2-4)-6(2+2) = 5(-2)-6(4) = -10-24 = -34 ..